System tools for system change. Issue 3 (30th November 2011) - Willis, Cameron D; Mitton, Craig; Gordon, Jason; Best, Allan
Abstract : Background: Health system transformations are influenced by dynamic relationships within and between individuals and institutions, as well as political, educational and legislative factors. This article aims to promote awareness of five tools that recognise this complexity and that are proposed to have value for decision makers: concept mapping, social network analysis, system dynamics modelling, programme budgeting and marginal analysis, and the tools for knowledge management and translation. Methods: The authors briefly describe the methodological approach of each tool, provide a commentary on the conditions in which these tools have been employed, and discuss their impact on the processes and outcomes of system transformation. An international advisory panel was convened based on a combination of experience, expertise and perspective. The panel assisted in synthesising the evidence relating to each tool and, in partnership with the authors, refined the interpretation of the role and value of each tool for system transformation. Findings: The tools discussed may impact the structural and procedural outcomes of transformation as well as the values, behaviours and attitudes of people undergoing change. The techniques described provide those undertaking transformation with methods to negotiate clinical, academic, political, organisational and cultural perspectives, and recognise the pivotal role of context in transformation. Conclusions: This review offers a novel synthesis of how these tools may add value to decision making for health policy. The tools discussed, while not a panacea to the challenges of large system change, provide methods that acknowledge the complexity of the transformative challenge and present innovative paths to co-produced solutions.